Analysis of the antioxidative function of the radioprotective Japanese traditional (Kampo) medicine, hangeshashinto, in an aqueous phase - Matsumoto, Chinami (J Radiat Res, 2015)
Oral mucositis (OM) is a common and painful complication of radiotherapy for head and neck cancer. Hangeshashinto (HST), a Japanese traditional medicine, is known to alleviate radiotherapy- and/or chemotherapy-induced OM; however, the detailed mechanism has not yet been clarified. The aim of the present study was to clarify the details of the antioxidative functions of HST against reactive oxygen species (ROS) produced by radiation. The hydroxyl radical (•OH)–scavenging ability and the reduction ability was simultaneously measured using a modified electron paramagnetic resonance (EPR) spin-trapping method. The superoxide (O(2)(•−))–scavenging ability was estimated by an EPR redox probing method. Water suspensions of powdered HST and of its seven constitutive crude drugs were tested. In addition, some of the main water-soluble ingredients of the crude drugs were also tested. HST was found to scavenge both •OH and O(2)(•−). Furthermore, HST was observed to reduce relatively stable nitroxyl radicals. Glycyrrhizae Radix (kanzo), Ginseng Radix (ninjin), Zizyphi Fructus (taiso) and glycyrrhizin (an ingredient of kanzo) were all found to be relatively good •OH scavengers. Scutellariae Radix (ogon) and Coptidis Rhizoma (oren) demonstrated reducing ability. In addition, acteoside and berberine chloride, which are water-soluble ingredients of ogon and oren, respectively, also demonstrated reducing ability. Oren exhibited oxidative ability at higher concentrations, which may have a function in maintaining catalytic redox action. The antioxidative function of HST probably worked via a balance of scavenging ROS, reducing stable free radicals, and some minor oxidizing activities.